A New capitalism in Brazil? Fusions & acquisitions on Lula government - Junior, José Carlos Martines Belieiro (Universidade Federal de Pelotas, 2018)
This paper aims analyze the phenomenon of fusions and acquisitions of companies in Brazil during the government of ex-president Luis Ignacio Lula da Silva, from 2003 to 2010. The adopted point of view is the one of relations between the State an d the economy trying to investigate what the new role of the private capital in the contemporary Brazil. The basic hypothesis that guide this work is to explain the fusions and acquisitions in a broader context of State support to the process of fusions and acquisitions as a new way of global insertion of Brazilian capitalism in a moment of international competitiveness.